2015
DOI: 10.1080/1059924x.2015.1106375
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression Symptoms Among Farmers: The HUNT Study, Norway

Abstract: Agriculture has undergone profound changes, and farmers face a wide variety of stressors. Our aim was to study the levels of anxiety and depression symptoms among Norwegian farmers compared with other occupational groups. Working participants in the HUNT3 Survey (The Nord-Trøndelag Health Study, 2006–2008), aged 19–66.9 years, were included in this cross-sectional study. We compared farmers (women, n = 317; men, n = 1,100) with HUNT3 participants working in other occupational groups (women, n = 13,429; men, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 23 publications
5
54
1
2
Order By: Relevance
“…Similar effects of other pesticides were noted in studies of Costa Rican banana farmers [21] and Colorado residents living on conventional farms [22]. Various sociodemographic and occupational factors that may exist in the farm environment, including limitation in farm infrastructure, weak family structure, farm economy, bureaucracy, and other farming related uncertainty, may generate stressors for these farmers and may put them at risk of mental health issues, including depression and anxiety [23].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Similar effects of other pesticides were noted in studies of Costa Rican banana farmers [21] and Colorado residents living on conventional farms [22]. Various sociodemographic and occupational factors that may exist in the farm environment, including limitation in farm infrastructure, weak family structure, farm economy, bureaucracy, and other farming related uncertainty, may generate stressors for these farmers and may put them at risk of mental health issues, including depression and anxiety [23].…”
Section: Introductionmentioning
confidence: 72%
“…Even though the response rate for the scale was 83%, the 'low' value of Cronbach's alpha revealed that the measure was fairly unidimensional. Several studies indicated that the combination of occupational and environmental stressors may contribute to increased risks of mental health outcomes and psychiatric disorders, such as suicide, even though information about these risk factors remains very limited [23,[34][35][36]. One study on 605 farm workers in the UK found that migrant organic farmworkers were happier and significantly less depressed than the conventional workers as they scored higher on Short Depression Happiness Scale (SDHS).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study is the first to use a sibling comparison design to investigate the mental health of farmers. Two large cross-sectional studies found that Norwegian farmers had high levels of symptoms of depression (5,6), and in our prospective analysis, we found that farmers had the highest odds of having symptoms of depression of all occupational groups in the study.…”
Section: Sibling Studymentioning
confidence: 66%
“…However, the evidence for whether the mental health of farmers differs from that of the general population is scarce and shows mixed results (1). Some studies have found that farmers had lower or similar prevalences of mental health problems compared to the general population or other rural residents (2-4), but two large population-based Norwegian studies found indications that farmers had the highest prevalence of depressive symptoms of all the occupational groups included in those studies (5,6).…”
mentioning
confidence: 99%
“…Farmers are known to experience higher rates of depression and anxiety in comparison to non-farmers (Browning et al 2008; Hounsome et al 2012; Torske et al 2016a; Torske et al 2016b). Estimates of depression prevalence among farmers have ranged from 8% to 20%, compared to a national prevalence of approximately 8% (Beseler et al 2008; CDC 2012).…”
Section: Introductionmentioning
confidence: 99%